Analysis of the Implementation of the 4P Marketing Mix Strategy (Product, Price, Place and Promotion) to Increase the Income of Boarding Business Actors - Diani; Jajo Firman Raharjo (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
Entering the era of globalization which is marked by the disappearance of boundaries between regions, as well as advances in the fields of science and technology which are increasingly massive, causing competition in the business world to be tighter. The emergence of competition between producers or business actors in marketing a product to the market is an absolute problem and challenge that cannot be avoided by a business actor. This study aims to analyze and find out what marketing strategies are used by business actors in increasing sales. The research method used is descriptive qualitative analysis, where the marketing strategy refers to the 4P marketing mix concept. The sample of this research is boarding house business actors, one of which is Nareswara Boarding House. Data collection techniques through documentation, interviews and observation. Data analysis techniques used are research documentation and descriptive analysis. Based on the analysis conducted in increasing the income of boarding house business actors using the 4P marketing mix. The results of this study can determine the application of the 4P marketing mix marketing strategy in an effort to increase the income of boarding house business actors and provide strategic recommendations delivered for the development of the boarding house business in the future.